Pharmacogenomics of 17‐alpha hydroxyprogesterone caproate for recurrent preterm birth: a case–control study. (31st January 2017) - Manuck, TA; Watkins, WS; Esplin, MS; Biggio, J; Bukowski, R; Parry, S; Zhan, H; Huang, H; Andrews, W; Saade, G; Sadovsky, Y; Reddy, UM; et al.
Abstract : Objective: To compare maternal genotypes between women with and without significant prolongation of pregnancy in the setting of 17‐alpha hydroxyprogesterone caproate (17‐P) administration for the prevention of recurrent preterm birth (PTB). Design: Case–control. Setting: Three tertiary‐care centres across the USA. Population: Women ( n  = 99) with ≥ 1 prior singleton spontaneous PTB, receiving 17‐P. Methods: Women were classified as having successful prolongation of pregnancy during the 17‐P treated pregnancy, in two ways: (1) Definition A: success/non‐success based on difference in gestational age at delivery between 17‐P‐treated and untreated pregnancies (success: delivered ≥ 3 weeks later with 17‐P) and (2) Definition B: success/non‐success based on reaching term (success: delivered at term with 17‐P). Main outcome measures: To assess genetic variation, all women underwent whole exome sequencing. Between‐group sequence variation was analysed with the Variant Annotation, Analysis, and Search Tool (VAAST). Genes scored by VAAST with P  < 0.05 were then analysed with two online tools: (1) Protein ANalysis THrough Evolutionary Relationships (PANTHER) and (2) Database for Annotation, Visualization, and Integrated Discovery (DAVID). Results: Using Definition A, there were 70 women with successful prolongation and 29 without; 1375 genes scored by VAAST had P  < 0.05. Using Definition B, 47 women had successful prolongation and 52 did not; 1039 genes scored by VAAST had P  < 0.05. PANTHER revealed key differences in gene ontology pathways. Many genes from definition A were classified as prematurity genes ( P  = 0.026), and those from definition B as pharmacogenetic genes ( P  = 0.0018); ( P, non‐significant after Bonferroni correction). Conclusion: A novel analytic approach revealed several genetic differences among women delivering early vs later with 17‐P. Tweetable abstract: Several key genetic differences are present in women with recurrent preterm birth despite 17‐P treatment. Tweetable abstract: Several key genetic differences are present in women with recurrent preterm birth despite 17‐P treatment.